Treatment Against Decay and Fire of Grasses and Palmyra Leaves Used for Thatching Roofs - Purushotham, A.; Rana, K. S. (Indian Forester, 1953)
In this paper details on the experiments to treat Nanal grass and palmyra leaves with suitable chemicals so as to protect them against fungi, insects and fire, are given. For purposes of comparison data on the annual charge for various common residential roofings are also worked out.